2019
DOI: 10.1109/access.2019.2929583
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Multi-Sink Nodes Path Planning Algorithm Concerned With Energy Balance in Wireless Sensor Networks

Abstract: In order to relieve the problem of unbalanced energy consumption of sensor nodes near the base station in the wireless sensor network, this paper proposes a mobile multi-sink nodes path planning algorithm with energy balance (hexHPSO). An optimization model is established by considering the energy consumption of each group, network lifetime, and movement path of the mobile sink nodes. Meanwhile, a hybrid positive and negative particle swarm optimization algorithm (HPNPSOA) is proposed to solve the optimization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Sun et al [23] presented hybrid positive and negative particle swarm optimization algorithm (HPNPSOA) to determine the optimal path for multiple mobile sinks and stop positions in hexagonal grids. The authors concluded that their proposed approach eliminated the energy hole problem, reduced network latency, and prolonged the network lifetime.…”
Section: A Optimized Mobile Sink Path Without Clusteringmentioning
confidence: 99%
“…Sun et al [23] presented hybrid positive and negative particle swarm optimization algorithm (HPNPSOA) to determine the optimal path for multiple mobile sinks and stop positions in hexagonal grids. The authors concluded that their proposed approach eliminated the energy hole problem, reduced network latency, and prolonged the network lifetime.…”
Section: A Optimized Mobile Sink Path Without Clusteringmentioning
confidence: 99%
“…Intelligent manufacturing has emerged with the rapid development of information technology. IWSNs are one of the key technologies of intelligent manufacturing, and they are a combination of IWSNs and the Internet of Things [1][2][3]. Compared with traditional wired industrial sensor networks, it has the characteristics of fast deployment, high flexibility, and self-organization.…”
Section: Introductionmentioning
confidence: 99%